PENGELOMPOKAN TINGKAT KEAMANAN WILAYAH JAWA TENGAH BERDASARKAN INDEKS KEJAHATAN DAN JUMLAH POS KEAMANAN DENGAN METODE KLASTERING K-MEANS - Retno Tri Vulandari (STMIK Sinar Nusantara, 2016)
The level of security in Central Java declined but for each region is not the case. Based on the crime index and the number of security posts in each police region of Central Java.These data are used for grouping the two regions in Central Java, namely good security level and bad security level.K-Means clustering method is a method used to classify data based on multiple attributes.K-Means clustering method is a method used to classify data based on multiple attributes. In this study, will be applied to the K-Means method with random initial centers. It is derived from two police regions that describe the good and bad security level.The formulation of the problem is to know the areas with good and bad security level in Central Java. Based on the results, there are 8areas with good security level and 27 areas with bad security level. Keyword :Crime Index, K-Means Clustering